Shadow State In The Management Of Shock Market In Marpoyan Damai Dictrict, Pekanbaru City (Study In Shock Market Pahlawan Kerja In Marpoyan Damai District) - Ahmad Fitra Yuza; Mochamad Andre Budiawan (UIR Press, 2021)
This research examines Shadows state in Management of shock Market. Marpoyan Damai District, Pekanbaru City (Study in the Shock Market Heroes Work, Marpoyan Damai District). This study aims to determine the Shadow Statein the Management of the Shock Market in Marpoyan Damai District, Pekanbaru City (Study in the Shock Market in Heroes of Work, Marpoyan Damai District). This type of research, which is located in the shock market of Work Heroes,Marpoyan Peace districts, is descriptive with a qualitative method, namely research that seeks to describe the object or subject under study in accordance with what it is, and to explain variables and indicators. The results of the research on Shadow Government in the Management of the Shock Market in Marpoyan Peace District, Pekanbaru City (Study in the Shock Market Hero of Work, Marpoyan Damai District) were analyzed through three indicator indicators. the first is Social Control or social control of the Pekanbaru City Government, the Marpoyan Damai District Government, and the Maharatu Village Government have carried out social control through curbing the management of the shock market but for the management of the shock market itself, the actors involved are local strongmen who have influential authority in the environment. people who do have the land to establish or organize the shocked market. Both Defense Strategies found that the market shock persisted even though it did not have an official permit because the market was able to meet the basic needs that were really needed by the community so that people prefer to make buying and selling transactionsin the shock market rather than the official market managed by the Pekanbaru City Government. Third Development of Local Existence, it is found that the local government is inferior to the existence of a local strongman, it can be seen through the ongoing market activity even though it does not have an official license or is included in an illegal market.